Helicobacter Pylori and Peptic Ulcer Disease - Muhammad S. Tahir (Pakistan Journal of Medical & Health Sciences, 2024)
Dear Editor, Peptic ulcer disease causes mucosal ulcers primarily in distal stomach and proximal duodenum, presenting as recurring pain in abdomen, bloating, and is often associated with nausea, vomiting and gastrointestinal bleed. The underlying mechanism involves a defect in mucosal protection and an increased gastric acid secretion causing the damage. Helicobacter Pylori, the use of nonsteroidal anti-inflammatory drugs, smoking and alcohol and are some of the common causative agents. H. Pylori affect about 50% of the population worldwide, especially in underdeveloped nations and is linked to chronic gastritis, B cell mucosa-associated lymphoma and gastric carcinoma. While some etiologies can be managed easily by lifestyle change, elimination of H. Pylori remains essential in preventing and treating gastrointestinal diseases.PAC therapy is a standard eradication strategy which uses proton pump inhibitors in conjunction with two antibiotics for up to 7-14 days.